A Class‐Based Analysis of Sustainable Development: Developing a Radical Perspective on Environmental Justice. (29th February 2012) - Deutz, Pauline
ABSTRACT Recent resurgence of interest in social aspects of sustainability has enjoined with on‐going debates on environmental justice and equity. However, discussions on the socio‐geographic distribution of environmental (dis‐) benefits have substantially overlooked the issue of class (as defined by Marx). This paper begins to address that deficit by presenting a new conceptualization of sustainable development explicitly drawing on Marxist theorizations of class. Capital and labour have a fundamental conflict of interest; governments have limited potential, or interest, in intervening on labour's behalf. Environmental policies have been portrayed as offering economic and social benefits including so‐called green jobs. This paper argues that such policies generate competition for investment rather than promoting equity. Green jobs may offer distributional benefits to individual workers, in certain locations, but cannot benefit labour as a class. Copyright © 2012 John Wiley & Sons, Ltd and ERP Environment.